Acute coronary syndrome care across Australia and New Zealand: the SNAPSHOT ACS study. Issue 3 (5th August 2013) - Chew, Derek P; French, John; Briffa, Tom G; Hammett, Christopher J; Ellis, Christopher J; Ranasinghe, Isuru; Aliprandi‐Costa, Bernadette J; Astley, Carolyn M; Turnbull, Fiona M; Lefkovits, Jeffrey; Redfern, Julie; Carr, Bridie; et al.
Abstract: Objectives: To characterise management of suspected acute coronary syndrome (ACS) in Australia and New Zealand, and to assess the application of recommended therapies according to published guidelines. Design, setting and patients: All patients hospitalised with suspected or confirmed ACS between 14 and 27 May 2012 were enrolled from participating sites in Australia and New Zealand, which were identified through public records and health networks. Descriptive and logistic regression analysis was performed. Main outcome measures: Rates of guideline‐recommended investigations and therapies, and inhospital clinical events (death, new or recurrent myocardial infarction [MI], stroke, cardiac arrest and worsening congestive heart failure). Results: Of 478 sites that gained ethics approval to participate, 286 sites provided data on 4398 patients with suspected or confirmed ACS. Patients' mean age was 67 years (SD, 15 years), 40% were women, and the median Global Registry of Acute Coronary Events (GRACE) risk score was 119 (interquartile range, 96–144). Most patients (66%) presented to principal referral hospitals. MI was diagnosed in 1436 patients (33%), unstable angina or likely ischaemic chest pain in 929 (21%), unlikely ischaemic chest pain in 1196 (27%), and 837 patients (19%) had other diagnoses not due to ACS. Of the patients with MI, 1019 (71%) were treated with angiography, 610 (43%) with percutaneous coronary intervention and 116 (8%) with coronary artery bypass grafting. Invasive management was less likely with increasing patient risk (GRACE score < 100, 90.1% v 101–150, 81.3% v 151–200, 49.4% v > 200, 36.1%; P < 0.001). The inhospital mortality rate was 4.5% and recurrent MI rate was 5.1%. After adjusting for patient risk and other variables, significant variations in care and outcomes by hospital classification and jurisdiction were evident. Conclusion: This first comprehensive combined Australia and New Zealand audit of ACS care identified variations in the application of the ACS evidence base and varying rates of inhospital clinical events. A focus on integrated clinical service delivery may provide greater translation of evidence to practice and improve ACS outcomes in Australia and New Zealand.